STUDENTS’ ENTREPRENEURIAL DEVELOMPENT IN US: DEFINITION, METHODS AND PRACTICAL TIPS - Сліпенко, Вікторія (Modern engineering and innovative technologies, 2024)
The article reveals definition, methods and practical tips of ensuring the development of entrepreneurial competence of students in secondary schools in the United States and characterizes them. Based on the method of conceptual and comparative analysis,